2018
DOI: 10.1111/bjet.12612
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' beliefs and technology acceptance concerning smart mobile devices for SMART education in South Korea

Abstract: Teachers' beliefs are a major factor in the effective use of new technology in teaching and learning. Recently, smart mobile devices (SMDs) such as smartphones, smart pads and tablet computers have been responsible for introducing broad innovations into the education field as Self‐directed, Motivated, Adaptive, Resources‐enriched, Technology embedded education in South Korea. Teachers' beliefs and technology acceptance concerning SMDs in South Korea can be either a facilitator or a barrier to the use of SMDs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 18 publications
3
51
0
3
Order By: Relevance
“…In line with the quantitative results, the teachers also revealed in the interview through qualitative data elaboration that the improvement of students' learning was the main reason for ICT integration in VTHSs which is in accordance with the study by Herman et al (2008). Further, benefits on student engagement and student learning, establishing communication and getting students more actively involved with variation of learning, and engaging activities outside the classroom as well as extended learning time are also informed in the qualitative findings which are related to behavioral beliefs for ICT use in VTHSs (Leem & Sung, 2018;Li, Yamaguchi & Takada, 2018). Qualitative data results also revealed that VTHS teachers believed that their students, administrators, and colleagues were the people who will most likely influence their normative beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the quantitative results, the teachers also revealed in the interview through qualitative data elaboration that the improvement of students' learning was the main reason for ICT integration in VTHSs which is in accordance with the study by Herman et al (2008). Further, benefits on student engagement and student learning, establishing communication and getting students more actively involved with variation of learning, and engaging activities outside the classroom as well as extended learning time are also informed in the qualitative findings which are related to behavioral beliefs for ICT use in VTHSs (Leem & Sung, 2018;Li, Yamaguchi & Takada, 2018). Qualitative data results also revealed that VTHS teachers believed that their students, administrators, and colleagues were the people who will most likely influence their normative beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Problems from the interview were revealed such as connection error, broken tools, and software update should be overcome by facilitating access to ICT and human resource support as also suggested from other previous research findings (Chen & Hudson, 2018;Khan & Markauskaite, 2016). There have been many researches reporting beliefs toward ICT and its integration in education (Herman et al, 2008;Leem & Sung, 2018;Li, Yamaguchi & Takada, 2018). However, little have been conducted in the context of vocational education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some countries, including Malaysia, MT integration among teachers is still not widely practiced, especially in secondary schools. The critical issue facing teachers is the level of integration of MT in enhancing teaching effectiveness [8], [9], [10]. Some teachers fear the use of technology devices will increase their workload and responsibility in teaching [8].…”
Section: Introductionmentioning
confidence: 99%
“…Some teachers fear the use of technology devices will increase their workload and responsibility in teaching [8]. Some teachers have a low attitude and confidence in their ability to enhance teaching through MT [9]. Besides, constraints such as location, student attitude and lack of emphasis on administration are the reason for teachers' readiness to integrate MT in the classroom [10].…”
Section: Introductionmentioning
confidence: 99%